Cytomegalovirus‐associated pseudomembranous colitis in a kidney transplant recipient. Issue 4 (23rd July 2021) - Chua, Yi Yi; Ho, Quan Yao; Ngo, Nye Thane; Krishnamoorthy, Thinesh Lee; Thangaraju, Sobhana; Kee, Terence; Wong, Hei Man
Abstract: Pseudomembranous colitis (PMC) is classically associated with Clostridium difficile infection. We report a rare case of cytomegalovirus (CMV)‐associated PMC in a 52‐year‐old female patient who had undergone kidney transplantation more than 20 years ago and was on low dose prednisolone and ciclosporin. She presented with an acute history of fever, lethargy, vomiting and diarrhoea on admission. Computed tomography of the abdomen showed extensive colitis, and colonoscopy revealed extensive pseudomembrane formation. Multiple tests for Clostridium difficile and other common microbiological causes of colitis were negative. CMV DNAemia and colonic biopsies confirmed the diagnosis of CMV colitis. The patient responded to prompt CMV treatment, as demonstrated by clinical, endoscopic, and histological response. While CMV is a common pathogen in the solid organ transplant population that is familiar to most transplant physicians, it may present atypically as PMC. Here, we review the literature on CMV‐associated PMC and its relevance to solid organ transplant recipients. To our knowledge, this is the first reported case of CMV‐associated PMC in a kidney transplant recipient.